1996
DOI: 10.1080/00288330.1996.9516739
|View full text |Cite
|
Sign up to set email alerts
|

Inflows of geothermal fluid chemicals to the Waikato River catchment, New Zealand

Abstract: Data collected from two monitoring programmes conducted by Environment Waikato, New Zealand, have been used to estimate the mass flows of Li, B, As, SO 4 , and Cl from geothermal fluids entering the Waikato River up stream of Lake Whakamaru. Chloride is the major anion in geothermal waters and is closely related to Li, B, and As. The total river water mass flow of Cl is 4600 g s -1 at the outlet of Lake Whakamaru and of this, 78% originates from geothermal fluids; 13% flows into Lake Taupo, and 65% enters the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thorsten et al [29] showed that concentrations of Mn, Zn, and Cu in Río Vacas Heladas (Chile) exceeded WHO guideline values for drinking water. Timperley et al [30] estimated that 78% of the Cl − in the Waikato River (New Zealand) comes from geothermal fluids. More and more studies are proving the impact of geothermal water on rivers related to river runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Thorsten et al [29] showed that concentrations of Mn, Zn, and Cu in Río Vacas Heladas (Chile) exceeded WHO guideline values for drinking water. Timperley et al [30] estimated that 78% of the Cl − in the Waikato River (New Zealand) comes from geothermal fluids. More and more studies are proving the impact of geothermal water on rivers related to river runoff.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As a consequence of this geothermal influence, elevated levels of arsenic have been identified along the Waikato River, in other waterways and biota across the TVZ. [18][19][20][21][22][23][24][25][26] For example, in a specific geothermally influenced area, the Reporoa Basin, 33% of the groundwater samples exceeded the New Zealand maximum acceptable value (MAV) for drinking water of 0.010 mg l À1 As, 27 with a maximum value of 0.556 mg l À1 As observed. 28 Several investigations have reported total and arsenic speciation in New Zealand geothermal waters and geothermally sourced rivers within the TVZ.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several investigations have reported total and arsenic speciation in New Zealand geothermal waters and geothermally sourced rivers within the TVZ. However, many of the reported levels are direct measurements of total arsenic only, 17,[20][21][22]24 total arsenic and arsenite species with arsenate by difference between total arsenic and arsenite, 28 total arsenic and both inorganic species, 19,29 or total arsenic with inferred arsenic speciation. Approaches taken to date have included: (1) estimation of probable forms of inorganic arsenic in geothermal fluids (often deep fluids) by combination of solubility measurements with chemical speciation calculations.…”
Section: Introductionmentioning
confidence: 99%